Preparation method of synergistically hardened and toughened WC-FeNiCo-CeO2 hard alloy material

By introducing CeO2 enhanced phase and FeNiCo medium entropy alloy adhesive into cemented carbide, combined with discharge plasma sintering technology, the problems of poor mechanical performance and scarce Co resources in high-temperature environments are solved, and the hardness and fracture toughness are significantly improved and cost reduction are achieved.

CN119609114AActive Publication Date: 2025-03-14HEFEI UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411804513.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-14
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

The existing cemented carbide materials have poor mechanical performance in high temperature environments, and are scarce in Co resources and high manufacturing costs, making it difficult to meet high performance needs.

Method used

CeO2 was introduced as the reinforced phase by wet chemistry method, and FeNiCo medium entropy alloy adhesive was used to replace Co, and WC-FeNiCo-CeO2 cemented carbide material was prepared in combination with discharge plasma sintering technology.

Benefits of technology

It significantly improves the hardness, fracture toughness and density of cemented carbide, reduces material costs, and is suitable for mechanical applications in high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure H69PZ1Z4WVRYGRXZAEOOE2KQYU8RDINFHUE9RBHA
    Figure H69PZ1Z4WVRYGRXZAEOOE2KQYU8RDINFHUE9RBHA
  • Figure JG2M8NLQPQPWUYYMQ09SVDJLMBWCJXWEIFC8HVAK
    Figure JG2M8NLQPQPWUYYMQ09SVDJLMBWCJXWEIFC8HVAK
  • Figure JUQYJH6GTWGN2D5HADGXGS0U9SRKVEWVLH3QKRFY
    Figure JUQYJH6GTWGN2D5HADGXGS0U9SRKVEWVLH3QKRFY
Patent Text Reader

Abstract

The invention discloses a preparation method of a synergistically hardened and toughened WC-FeNiCo-CeO2 hard alloy material. The preparation method specifically comprises the following steps: (1) preparing W-CeO2 composite powder; (2) preparing an entropy alloy adhesive in FeNiCo; (3) preparation of WC-FeNiCo-CeO2 composite powder is carried out; and (4) spark plasma sintering. CeO2 is introduced through a wet chemical method to serve as a reinforcing phase, it is guaranteed that trace additives are evenly distributed in the whole composite powder, grain boundaries are purified, the wettability of the grain boundaries and a binding phase is improved, gaps are promoted to be filled with a liquid phase, and the porosity of the alloy is reduced; co is replaced by a FeNiCo medium-entropy alloy adhesive, so that the material cost is reduced, and the hardness and the fracture toughness are improved; the hard alloy composite material which is high in density, uniform in grain structure, excellent in mechanical property and wider in application range is prepared through spark plasma sintering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of cemented carbide strengthening, and specifically relates to a synergistically hardened and toughened WC-FeNiCo-CeO 2 Preparation method of cemented carbide material. Background Art

[0002] Cemented carbide is an excellent alloy material, which is made of carbides of high-hardness refractory metals (such as WC and TiC) and bonding metals (such as Co, Ni, Mo) through advanced powder metallurgy technology. This material not only has extremely high hardness and strength, but also has excellent wear resistance and corrosion resistance, and is praised as the "industrial teeth". Cemented carbide has a very wide range of applications, covering military industry, aerospace, mechanical processing, metallurgy, oil drilling, mining tools, electronic communications, and construction. In order to meet the high performance requirements brought about by the progress of the times, it is necessary to further improve the comprehensive mechanical properties of cemented carbide.

[0003] Cobalt (Co) is the most widely used binder in cemented carbide production. It is highly favored for its excellent comprehensive performance, but its resource scarcity and high cost have become one of the key factors restricting the development of cemented carbide. Fe and Ni can be used as alternative binders because of their similar properties to Co. Ni can form a protective film on the surface due to its passivation properties, which helps to improve corrosion resistance. In addition, the addition of Ni can also improve the thermal stability of cemented carbide, so that it can maintain good mechanical properties under high temperature environment; Fe can help refine WC grains, thereby improving the wear resistance of cemented carbide. Therefore, by accurately controlling the composition ratio in the Fe-Ni-Co ternary system and the microstructure design, the overall performance of cemented carbide can be precisely controlled to meet the specific needs of different application scenarios.

[0004] The preparation of WC-FeNiCo by ordinary sintering technology requires long-term high-temperature sintering, which not only increases the production cycle and cost, but also causes problems of sample structure inhomogeneity and low density. Spark plasma sintering (SPS) is a new technology that uses pulse current to directly sinter. Compared with ordinary sintering technology, it has the advantages of fast sintering, low-temperature sintering, high uniformity and controllable microstructure. During the sintering process, CeO 2 It can be used as a sintering aid to promote the densification process of the alloy, improve the density and strength of the alloy, and add appropriate CeO 2 It can also improve the fracture toughness of cemented carbide. Summary of the invention

[0005] In order to solve the problems raised in the background technology, the present invention aims to provide a synergistically hardened and toughened WC-FeNiCo-CeO 2The invention discloses a method for preparing a cemented carbide material. The method has low material cost, can make the reinforcement phase evenly distributed in the matrix, and the mechanical properties and fracture toughness of the prepared WC-based cemented carbide material are significantly improved.

[0006] The technical solution of the present invention: A synergistic hardening and toughening WC-FeNiCo-CeO 2 The preparation method of cemented carbide material specifically comprises the following steps: (1) W-CeO 2 Preparation of composite powder Add an appropriate amount of ammonium metatungstate (NH 4 ) 2 WO 4 ) and cerium nitrate (Ce(NO 3 ) 3 ), after the two reagents are fully dissolved and evenly mixed, continue to add an appropriate amount of oxalic acid to the solution to adjust the pH value of the solution to the required range (pH value is 7~9), then, heat the solution at a certain temperature and continue to stir until the solution evaporates and concentrates to form a precursor precipitate; then, place the precipitate in a drying oven for drying for several hours until the water therein is completely removed, crush the dried precipitate, and sieve it with a standard sieve to ensure that a composite precursor powder with uniform particle size is obtained; finally, put the composite precursor powder in a high-purity alumina crucible, place it in a muffle furnace for high-temperature calcination, and then transfer the sample to a high-temperature tubular atmosphere furnace for high-temperature reduction treatment, and finally prepare the desired W-CeO 2 Composite powder materials; (2) Preparation of FeNiCo medium entropy alloy adhesive Weigh high-purity Fe powder, Ni powder and Co powder respectively and place them in a ball mill, add carbide balls, set the ball-to-material ratio to 10:1, add anhydrous ethanol and mix and mill in a ball mill to obtain a uniformly mixed powder slurry, then dry it in a drying oven and sieve it to obtain a FeNiCo medium-entropy alloy binder; (3) WC-FeNiCo-CeO 2 Preparation of composite powder The W-CeO prepared in step (1) 2 The composite powder and an appropriate amount of carbon black are placed in a ball mill, and carbide grinding balls are added. The ball mill is assembled under the protection of argon. After the assembly is completed, the ball mill is fixed in a planetary ball mill for several hours, and then placed in a high-temperature tubular atmosphere furnace for carbonization to obtain WC-CeO 2 Composite powder; then weigh WC-CeO according to the designed component ratio 2The composite powder and the FeNiCo powder obtained in step (2) are mixed and ball-milled in a ball mill equipped with carbide grinding balls and anhydrous ethanol, and then the ball-milled mixed powder slurry is placed in a drying oven for drying for several hours until the moisture therein is completely removed, and the precipitate obtained by drying is crushed and sieved using a standard sieve to obtain WC-FeNiCo-CeO with uniform particle size. 2 Composite powder; (4) Spark plasma sintering The WC-FeNiCo-CeO obtained in step (3) 2 The composite powder was loaded into a graphite mold, and the composite powder was pre-pressed using a hydraulic press. The treated mold was then placed in a spark plasma sintering furnace, and the furnace chamber was vacuumed at room temperature. The temperature was raised to 600°C and kept for 5 minutes to allow the residual gas to be discharged. The temperature was then raised to 1200-1300°C and kept for 5 minutes before sintering. The sample was cooled with the furnace, thereby obtaining high-performance WC-FeNiCo-CeO 2 Cemented carbide composite materials.

[0007] In the step (1), ammonium metatungstate (NH 4 ) 2 WO 4 ) and cerium nitrate (Ce(NO 3 ) 3 ) according to the quality of the WC-FeNiCo-CeO 2 WC and CeO in cemented carbide 2 The amount of oxalic acid added is calculated as follows: ammonium metatungstate (NH 4 ) 2 WO 4 ) and cerium nitrate (Ce(NO 3 ) 3 ) is 39.0% of the total mass, and is heated in an oil bath at a temperature of 120~150℃.

[0008] The drying oven in step (1) is an electric constant temperature blast drying oven, model DHG-9070, with a temperature setting of 80-100°C and a drying time of 8-12 hours.

[0009] In step (1), the temperature of the muffle furnace is set to 500-600° C., and the time is set to 4-5 hours.

[0010] In the step (1), the composite precursor powder is reduced in a high-temperature tubular atmosphere furnace to generate W-CeO 2 The reduction temperature of the composite powder is 800~900℃, the reduction time is 2~3h, and the hydrogen flow rate is 4m 3 / h.

[0011] In the step (2), the mass ratio of Fe powder, Ni powder and Co powder is 1:2:2.

[0012] The ball mill in step (2) is a QM-QX4 omnidirectional planetary ball mill produced by Nanjing University of Science and Technology. The ball mill speed (rotation speed) is 350 rpm, the ball-to-material ratio is set to 10:1, the ball milling time is set to 30 h, and the ball tank and the ball milling medium are both made of cemented carbide.

[0013] The drying oven in step (2) is an electric constant temperature blast drying oven, model DHG-9070, with a temperature setting of 80-100°C and a drying time of 8-12 hours.

[0014] The amount of carbon black added in step (3) is based on the W-CeO 2 The composite powder accounts for 6.14% of the total mass of the composite powder. The dry mixing time in the planetary ball mill is 4 to 8 hours, the speed is set at 300 to 400 r / min, and the ball-to-material ratio is set at 10:1.

[0015] In step (3), the tungsten-carbon composite powder is loaded into an alumina crucible and placed in a high-temperature tubular atmosphere furnace for high-temperature carbonization at a temperature of 1400-1550°C, a reaction time of 2-3 hours, and a hydrogen flow rate of 4 m 3 / h, and after cooling in the furnace, the composite powder was ground and sieved through 80 meshes to obtain WC-CeO 2 Composite powder.

[0016] The amount of FeNiCo powder added in step (3) is based on the WC-FeNiCo-CeO 2 10% of the total mass of the composite powder was prepared and wet-milled in a planetary ball mill for 30-40 hours, with the speed set at 350 r / min and the ball-to-material ratio set at 10:1; The drying oven in step (3) is an electric constant temperature blast drying oven, model DHG-9070, with a temperature setting of 80-100°C and a drying time of 8-12h.

[0017] In step (4), the diameter of the graphite mold is 25 mm, and the WC-FeNiCo-CeO 2 Carbon paper is used to isolate the final processed composite powder from the graphite mold to facilitate sampling and demoulding after sintering.

[0018] In the step (4), the pre-compacting pressure is 20 MPa, and infrared temperature measurement is used during sintering, with the infrared detector being aligned with the temperature measuring hole of the graphite mold.

[0019] The spark plasma sintering furnace model in step (4) is LaboxTM-300, and the setting program is as follows: increase the temperature to 600°C at a rate of 100°C / min, the sintering pressure is 20MPa, and keep warm for 5 minutes; then increase the temperature to 1230°C at a rate of 100°C / min, during which the pressure is increased from 20MPa to 40MPa, keep warm for 5 minutes, and then cool with the furnace.

[0020] Beneficial effects of the present invention: (1) The present invention introduces CeO by wet chemical method 2 As a reinforcing phase, the additive and the matrix are evenly mixed at the molecular level to ensure that the trace additive is evenly distributed in the entire composite powder, thereby maximizing the function of the additive. At the same time, this method can also purify the grain boundary, improve the wetting properties of the grain boundary and the bonding phase, promote the filling of the voids by the liquid phase, and reduce the porosity of the alloy; using FeNiCo medium entropy alloy binder to replace Co can not only reduce the cost of the material, but also improve the hardness and fracture toughness; finally, the spark plasma sintering technology is used to prepare WC-FeNiCo-CeO with high density, uniform grain structure, superior mechanical properties and a wider range of applications. 2 New cemented carbide composite material; (2) The new cemented carbide prepared by the present invention exhibits excellent performance, with a hardness of 1647 HV and a fracture toughness of 20.38 MPa·m 1 / 2 Compared with the conventional cemented carbide using only Co as binder (hardness 1483 HV, fracture toughness 12.15 MPa·m 1 / 2 ) has been significantly improved. In addition, the density of this new cemented carbide has also been improved, indicating that its microstructure is more compact, which means better mechanical properties and service life. Such progress is of great significance for applications that require high hardness and good toughness (such as cutting tools, mold manufacturing, etc.). BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 WC-10%FeNiCo-1.2%CeO prepared in Example 2 2 SEM image of the new cemented carbide material.

[0022] Figure 2 WC-10%FeNiCo-1.2%CeO prepared in Example 2 2 EDS image of new cemented carbide material.

[0023] Figure 3 WC-10%FeNiCo-1.2%CeO prepared in Example 2 2 Indentation image of the new cemented carbide material. DETAILED DESCRIPTION

[0024] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments.

[0025] Example 1 In this embodiment, the WC cemented carbide material toughened by the rare earth oxide and the medium entropy alloy binder is obtained by high temperature carburization on the basis of the additive modified tungsten powder obtained by the composite salt, ball milling with the medium entropy alloy binder and spark plasma sintering. 2 The components in the composite powder are composed of the following components by mass percentage (WC: 89.4%, FeNiCo: 10%, CeO 2 :0.6%).

[0026] In this embodiment, WC-FeNiCo-CeO 2 The material preparation method is as follows: (1) W-CeO 2 Preparation of composite powder First, according to the composition ratio of this embodiment, ammonium metatungstate ((NH 4 ) 2 WO 4 ) and cerium nitrate (Ce(NO 3 ) 3 ) is dissolved in deionized water. After the two reagents are fully dissolved and evenly mixed, an appropriate amount of oxalic acid is added to the solution. The amount of oxalic acid added is ammonium metatungstate (NH 4 ) 2 WO 4 ) and cerium nitrate (Ce(NO 3 ) 3 ) to adjust the pH value of the solution to the required range (pH value is 7-9), then heat the solution to 120°C in an oil bath and continue stirring until the solution evaporates and concentrates to form a precursor precipitate; then, place the precipitate in a blast drying oven for drying at 80°C for 8 hours, crush the dried precipitate, and sieve it with an 80-mesh standard sieve to ensure that a composite precursor powder with uniform particle size is obtained; finally, place the composite precursor powder in a high-purity alumina crucible, place it in a muffle furnace and calcine it at 550°C for 4 hours, then transfer the sample to a high-temperature tubular atmosphere furnace and reduce it at 800°C for 3 hours, and finally prepare the desired W-CeO 2 Composite powder materials; (2) Preparation of FeNiCo medium entropy alloy adhesive High-purity Fe powder, Ni powder and Co powder with a mass ratio of 1:2:2 were weighed and placed in a ball mill, and hard alloy balls were added. The ball-to-material ratio was set to 10:1, and anhydrous ethanol was added for mixed ball milling at a speed of 350 r / min. The mixed powder slurry was obtained by ball milling for 30 hours, and then placed in an electric constant temperature blast drying oven at 80°C for 8 hours, and sieved with a 80-mesh standard sieve to obtain a FeNiCo medium-entropy alloy adhesive; (3) WC-FeNiCo-CeO 2 Preparation of composite powder The W-CeO obtained in step (1) 2 The mixed powder and an appropriate amount of carbon black are placed in a ball mill. The amount of carbon black added is W-CeO 2 6.14% of the total mass of the composite powder, carbide grinding balls were added, and the ball-to-material ratio was 10:1. The ball mill was assembled under the protection of argon. After assembly, the ball mill was fixed in a planetary ball mill for 6 hours at a speed of 350r / min, and then placed in a high-temperature tubular atmosphere furnace for carbonization. The carbonization temperature was set to 1500℃, the reaction time was 2h, and the hydrogen flow rate was 4m 3 / h, thus obtaining WC-CeO 2 Composite powder; then weigh WC-CeO according to the designed component ratio 2 The composite powder and the FeNiCo powder obtained in step (2) are placed in a ball mill equipped with carbide grinding balls and anhydrous ethanol and mixed and ball milled, the ball-to-material ratio is 10:1, the ball milling time is 30 hours, and the rotation speed is 350r / min; then the ball-milled mixed powder slurry is placed in a blast drying oven at 80°C and dried for 8 hours, the precipitate obtained by drying is crushed, and sieved using an 80-mesh standard sieve to obtain WC-FeNiCo-CeO with uniform particle size. 2 Composite powder; (4) Spark plasma sintering The WC-FeNiCo-CeO obtained in step (3) 2 The composite powder was loaded into a graphite mold, and the composite powder was pre-pressed using a hydraulic press. The treated mold was then placed in a spark plasma sintering furnace, and the furnace chamber was vacuumed at room temperature. The heating rate was 100°C / min, and the temperature was first raised to 600°C and kept at this temperature for 5 minutes. The pressure was 20MPa to allow the residual gas to be discharged, and then the temperature was raised to 1230°C and the pressure was increased to 40MPa. After keeping the temperature for 5 minutes, the sintering was terminated and the sample was allowed to cool with the furnace. Thus, high-performance WC-FeNiCo-CeO 2 Cemented carbide composite materials.

[0027] Example 2 In this embodiment, the WC cemented carbide material toughened by the rare earth oxide and the medium entropy alloy binder is obtained by high temperature carburization on the basis of the additive modified tungsten powder obtained by the composite salt, ball milling with the medium entropy alloy binder and spark plasma sintering. 2 The components in the composite powder are composed of the following components by mass percentage (WC: 88.8%, FeNiCo: 10%, CeO 2 : 1.2%).

[0028] In this embodiment, WC-FeNiCo-CeO 2 The material preparation method is as follows: (1) W-CeO 2 Preparation of composite powder First, according to the composition ratio of this embodiment, ammonium metatungstate (NH 4 ) 2 WO 4 ) and cerium nitrate (Ce(NO 3 ) 3 ) is dissolved in deionized water. After the two reagents are fully dissolved and evenly mixed, an appropriate amount of oxalic acid is added to the solution. The amount of oxalic acid added is ammonium metatungstate (NH 4 ) 2 WO 4 ) and cerium nitrate (Ce(NO 3 ) 3 ) to adjust the pH value of the solution to the required range (pH value is 7-9), then heat the solution to 120°C in an oil bath and continue stirring until the solution evaporates and concentrates to form a precursor precipitate; then, place the precipitate in a blast drying oven for drying at 80°C for 8 hours, crush the dried precipitate, and sieve it with an 80-mesh standard sieve to ensure that a composite precursor powder with uniform particle size is obtained; finally, place the composite precursor powder in a high-purity alumina crucible, place it in a muffle furnace and calcine it at 550°C for 4 hours, then transfer the sample to a high-temperature tubular atmosphere furnace and reduce it at 800°C for 3 hours, and finally prepare the desired W-CeO 2 Composite powder materials; (2) Preparation of FeNiCo medium entropy alloy adhesive High-purity Fe powder, Ni powder and Co powder in a mass ratio of 1:2:2 were weighed and placed in a ball mill, and hard alloy balls were added. The ball-to-material ratio was set to 10:1, and anhydrous ethanol was added for mixed ball milling at a speed of 350 r / min. The mixed powder slurry was obtained by ball milling for 30 hours, and then placed in a drying oven at 80°C for 8 hours, and sieved with a 80-mesh standard sieve to obtain a FeNiCo medium-entropy alloy adhesive; (3) WC-FeNiCo-CeO 2 Preparation of composite powder The W-CeO obtained in step (1) 2 The mixed powder and an appropriate amount of carbon black are placed in a ball mill. The amount of carbon black added is W-CeO 2 6.14% of the total mass of the composite powder, carbide grinding balls were added, and the ball-to-material ratio was 10:1. The ball mill was assembled under the protection of argon. After assembly, the ball mill was fixed in a planetary ball mill for 6 hours at a speed of 350r / min, and then placed in a high-temperature tubular atmosphere furnace for carbonization. The carbonization temperature was set to 1500℃, the reaction time was 2h, and the hydrogen flow rate was 4m 3 / h, thus obtaining WC-CeO 2 Composite powder; then weigh WC-CeO according to the designed component ratio 2 The composite powder and the FeNiCo powder obtained in step (2) are placed in a ball mill equipped with carbide grinding balls and anhydrous ethanol and mixed and ball milled, the ball-to-material ratio is 10:1, the ball milling time is 30 hours, and the rotation speed is 350r / min; then the ball-milled mixed powder slurry is placed in a blast drying oven at 80°C and dried for 8 hours, the precipitate obtained by drying is crushed, and sieved using an 80-mesh standard sieve to obtain WC-FeNiCo-CeO with uniform particle size. 2 Composite powder; (4) Spark plasma sintering The WC-FeNiCo-CeO obtained in step (3) 2 The composite powder was loaded into a graphite mold, and the composite powder was pre-pressed using a hydraulic press. The treated mold was then placed in a spark plasma sintering furnace, and the furnace chamber was vacuumed at room temperature. The heating rate was 100°C / min, and the temperature was first raised to 600°C and kept at this temperature for 5 minutes. The pressure was 20MPa to allow the residual gas to be discharged, and then the temperature was raised to 1230°C and the pressure was increased to 40MPa. After keeping the temperature for 5 minutes, the sintering was terminated and the sample was allowed to cool with the furnace. Thus, high-performance WC-FeNiCo-CeO 2 Cemented carbide composite materials.

[0029] Example 3 In this embodiment, the WC cemented carbide material toughened by the rare earth oxide and the medium entropy alloy binder is obtained by high temperature carburization on the basis of the additive modified tungsten powder obtained by the composite salt, ball milling with the medium entropy alloy binder and spark plasma sintering. 2 The components in the composite powder are composed of the following components by mass percentage (WC: 88.2%, FeNiCo: 10%, CeO 2 : 1.8%).

[0030] In this embodiment, WC-FeNiCo-CeO 2 The material preparation method is as follows: (1) W-CeO 2 Preparation of composite powder First, according to the composition ratio of this embodiment, ammonium metatungstate (NH 4 ) 2 WO 4 ) and cerium nitrate (Ce(NO 3 ) 3 ) is dissolved in deionized water. After the two reagents are fully dissolved and evenly mixed, an appropriate amount of oxalic acid is added to the solution. The amount of oxalic acid added is ammonium metatungstate (NH 4 ) 2 WO 4 ) and cerium nitrate (Ce(NO 3 ) 3 ) to adjust the pH value of the solution to the required range (pH value is 7-9), then heat the solution to 120°C in an oil bath and continue stirring until the solution evaporates and concentrates to form a precursor precipitate; then, place the precipitate in a blast drying oven for drying at 80°C for 8 hours, crush the dried precipitate, and sieve it with an 80-mesh standard sieve to ensure that a composite precursor powder with uniform particle size is obtained; finally, place the composite precursor powder in a high-purity alumina crucible, place it in a muffle furnace and calcine it at 550°C for 4 hours, then transfer the sample to a high-temperature tubular atmosphere furnace and reduce it at 800°C for 3 hours, and finally prepare the desired W-CeO 2 Composite powder materials; (2) Preparation of FeNiCo medium entropy alloy adhesive High-purity Fe powder, Ni powder and Co powder in a mass ratio of 1:2:2 were weighed and placed in a ball mill, and hard alloy balls were added. The ball-to-material ratio was set to 10:1, and anhydrous ethanol was added for mixed ball milling at a speed of 350 r / min. The mixed powder slurry was obtained by ball milling for 30 hours, and then placed in a drying oven at 80°C for 8 hours, and sieved with a 80-mesh standard sieve to obtain a FeNiCo medium-entropy alloy adhesive; (3) WC-FeNiCo-CeO 2 Preparation of composite powder The W-CeO obtained in step (1) 2 The mixed powder and an appropriate amount of carbon black are placed in a ball mill. The amount of carbon black added is W-CeO 26.14% of the total mass of the composite powder, carbide grinding balls were added, and the ball-to-material ratio was 10:1. The ball mill was assembled under the protection of argon. After assembly, the ball mill was fixed in a planetary ball mill for 6 hours at a speed of 350r / min, and then placed in a high-temperature tubular atmosphere furnace for carbonization. The carbonization temperature was set to 1500℃, the reaction time was 2h, and the hydrogen flow rate was 4m 3 / h, thus obtaining WC-CeO 2 Composite powder; then weigh WC-CeO according to the designed component ratio 2 The composite powder and the FeNiCo powder obtained in step (2) are placed in a ball mill equipped with carbide grinding balls and anhydrous ethanol and mixed and ball milled, the ball-to-material ratio is 10:1, the ball milling time is 30 hours, and the rotation speed is 350r / min; then the ball-milled mixed powder slurry is placed in a blast drying oven at 80°C and dried for 8 hours, the precipitate obtained by drying is crushed, and sieved using an 80-mesh standard sieve to obtain WC-FeNiCo-CeO with uniform particle size. 2 Composite powder; (4) Spark plasma sintering The WC-FeNiCo-CeO obtained in step (3) 2 The composite powder was loaded into a graphite mold, and the composite powder was pre-pressed using a hydraulic press. The treated mold was then placed in a spark plasma sintering furnace, and the furnace chamber was vacuumed at room temperature. The heating rate was 100°C / min, and the temperature was first raised to 600°C and kept at this temperature for 5 minutes. The pressure was 20MPa to allow the residual gas to be discharged, and then the temperature was raised to 1230°C and the pressure was increased to 40MPa. After keeping the temperature for 5 minutes, the sintering was terminated and the sample was allowed to cool with the furnace. Thus, high-performance WC-FeNiCo-CeO 2 Cemented carbide composite materials.

[0031] Comparative Example 1 The WC-Co material in this comparative example is made by high-energy ball milling and spark plasma sintering, wherein the mass fraction of Co is preset to 10%, and the rest is WC.

[0032] The preparation method of WC-Co material in this comparative example is as follows: (1) Preparation of WC-Co composite powder WC powder and Co powder were weighed according to the composition ratio and loaded into a ball mill. The ball milling medium was anhydrous ethanol. The ball milling time was set to 30 h, the ball-to-material ratio was 10:1, and the ball milling speed was set to 350 r / min. The obtained slurry was transferred to a blast drying oven, where the drying temperature was 80 ° C and the drying time was 6 h. The dried precipitate was crushed and sieved with an 80-mesh standard sieve to ensure that the WC-Co composite powder with uniform particle size was obtained. (2) Spark plasma sintering The above-mentioned WC-10Co composite powder is added to a graphite mold wrapped with carbon paper, and then the graphite mold is placed in the furnace chamber of a spark plasma sintering furnace; the infrared is aimed at the temperature measuring hole of the graphite mold; the cavity door is closed to vacuum the furnace chamber, and after the furnace chamber reaches the vacuum level, the program is set for sintering. The sintering program is as follows: increase the temperature to 600°C at a rate of 100°C / min, keep warm for 5 minutes, then increase the temperature to 1230°C and keep warm for 5 minutes, and cool with the furnace after the insulation is completed. The pressure during sintering is 40MPa, and a WC-10%Co cemented carbide composite material is obtained after the sintering is completed.

[0033] Comparative Example 2 The WC-FeNiCo material in this comparative example is made by high-energy ball milling and spark plasma sintering, wherein the mass fraction of FeNiCo is preset to 10%, and the rest is WC.

[0034] (1) Preparation of FeNiCo medium entropy alloy binder High-purity Fe powder, Ni powder and Co powder in a mass ratio of 1:2:2 were weighed and placed in a ball mill, and hard alloy balls were added. The ball-to-material ratio was set to 10:1, and anhydrous ethanol was added for mixed ball milling at a speed of 350 r / min. The mixed powder slurry was obtained by ball milling for 30 hours, and then placed in a drying oven at 80°C for 8 hours, and sieved with a 80-mesh standard sieve to obtain a FeNiCo medium-entropy alloy adhesive; (2) Preparation of WC-FeNiCo composite powder Add an appropriate amount of WC powder and the FeNiCo powder obtained in step (2) according to the designed component ratio, place them in a ball mill, add cemented carbide balls, set the ball-to-material ratio to 10:1, and add anhydrous ethanol for mixed ball milling, the ball milling time is 30 hours, and the rotation speed is 350r / min; obtain a uniformly mixed powder slurry, then place it in a blast drying oven for drying at 80°C for 8 hours, and use an 80-mesh standard sieve for sieving to obtain a WC-FeNiCo composite powder with uniform particle size; (3) Spark plasma sintering The WC-FeNiCo composite powder obtained in step (2) is loaded into a graphite mold, and the composite powder is pre-pressed by a hydraulic press, and then the treated mold is placed in a spark plasma sintering furnace, and the furnace cavity is vacuumed at room temperature. The heating rate is 100°C / min, firstly the temperature is raised to 600°C and kept at this temperature for 5 minutes, the pressure is 20MPa, so that the residual gas can be discharged, and then the temperature is raised to 1230°C, the pressure is increased to 40MPa, and the sintering is terminated after keeping the temperature for 5 minutes, and the sample is allowed to cool with the furnace, thereby obtaining a high-performance WC-10%FeNiCo cemented carbide composite material.

[0035] The performance tests were conducted on the cemented carbide composite materials obtained in Examples 1 to 3 of the present invention and Comparative Examples 1 to 2. The test results are shown in Table 1: Table 1 Comparison of hardness and fracture toughness test results of cemented carbide composite materials of Examples 1-3 and Comparative Examples 1-2 As can be seen from Table 1, the present invention introduces CeO by wet chemical method. 2 As a reinforcing phase, the additive and the matrix are evenly mixed at the molecular level to ensure that the trace additive is evenly distributed in the entire composite powder, so as to maximize the function of the additive; using FeNiCo medium entropy alloy binder to replace Co can not only reduce the cost of the material, but also improve the hardness and fracture toughness; finally, the bulk material is prepared by spark plasma sintering to prepare WC-FeNiCo-CeO with high density, uniform grain structure, superior mechanical properties and wider application range. 2 New cemented carbide composite material. By comparison, it is found that adding appropriate CeO 2 It can also improve the fracture toughness of cemented carbide. In general, the hardness and fracture toughness of the cemented carbide composite material prepared by the composition design and preparation process of the present invention are good. 2 When the addition amount is 1.2%, the hardness and fracture toughness of the cemented carbide composite material are increased to the maximum value, which are 1647 HV and 20.38 MPa·m 1 / 2 , and the density of the material is also improved.

[0036] Depend on Figure 1 It can be seen that the grain size of the cemented carbide composite material of the present invention is uniform and small, and no defects or impurities are found.

[0037] Depend on Figure 2 It can be seen that the elements are evenly distributed from the energy spectrum analysis, indicating that the reinforcement phase is evenly distributed in the WC matrix and is tightly bonded to the interface of the WC matrix. Such a structure not only improves the overall strength of the material, but also enhances its wear resistance and crack resistance.

[0038] Depend on Figure 3 It can be seen that WC-10%FeNiCo-1.2%CeO 2 There are no cracks near the indentation, indicating that the material has very good toughness.

[0039] The above embodiments only illustrate specific implementations of the present disclosure, but the implementations of the present disclosure are not limited by the above contents. Any changes, modifications, substitutions, combinations, and simplifications made without substantially departing from the main idea and principle of the inventive concept of the present disclosure shall be equivalent replacement methods and shall be included in the scope of protection determined by the claims.

Claims

1. A method for preparing a synergistically hardened and toughened WC-FeNiCo-CeO2 cemented carbide material, characterized in that: The specific steps include: (1) Preparation of W-CeO2 composite powder Add appropriate amounts of ammonium metatungstate ((NH4)2WO4) and cerium nitrate (Ce(NO3)3) to deionized water. After the two reagents are fully dissolved and evenly mixed, continue to add appropriate amounts of oxalic acid to the solution to adjust the pH value of the solution to the desired range. Subsequently, heat the solution at a certain temperature and continue stirring until the solution evaporates and concentrates to form a precursor precipitate. After that, place the precipitate in a drying oven for drying for several hours until the water therein is completely removed. The dried precipitate is crushed and sieved with a standard sieve to ensure that a composite precursor powder with uniform particle size is obtained. Finally, the composite precursor powder is placed in a high-purity alumina crucible, and is placed in a muffle furnace for high-temperature calcination. The sample is then transferred to a high-temperature tubular atmosphere furnace for high-temperature reduction treatment, and the desired W-CeO2 composite powder material is finally prepared. (2) Preparation of FeNiCo medium entropy alloy adhesive Weigh high-purity Fe powder, Ni powder and Co powder respectively and place them in a ball mill, add carbide balls, set the ball-to-material ratio to 10:1, add anhydrous ethanol and mix and mill in a ball mill to obtain a uniformly mixed powder slurry, then dry it in a drying oven and sieve it to obtain a FeNiCo medium-entropy alloy binder; (3) Preparation of WC-FeNiCo-CeO2 composite powder The W-CeO2 composite powder obtained in step (1) and an appropriate amount of carbon black are placed in a ball mill, carbide grinding balls are added, and the ball mill is assembled under the protection of argon. After the assembly is completed, the ball mill is fixed in a planetary ball mill for ball milling for several hours, and then placed in a high-temperature tubular atmosphere furnace for carbonization to obtain a WC-CeO2 composite powder; then the WC-CeO2 composite powder and the FeNiCo powder obtained in step (2) are weighed according to the designed component ratio, and placed in a ball mill equipped with carbide grinding balls and anhydrous ethanol for mixed ball milling, and then the ball-milled mixed powder slurry is placed in a drying oven for drying for several hours until the moisture therein is completely removed, and the precipitate obtained by drying is crushed and sieved using a standard sieve to obtain a WC-FeNiCo-CeO2 composite powder with uniform particle size; (4) Spark plasma sintering The WC-FeNiCo-CeO2 composite powder obtained in step (3) is loaded into a graphite mold, and the composite powder is first pre-pressed by a hydraulic press, and then the treated mold is placed in a spark plasma sintering furnace, and the furnace chamber is vacuum-drawn at room temperature, and the temperature is raised to 600°C and kept warm for 5 minutes to allow residual gas to be discharged, and then the temperature is raised to 1200-1300°C, and the sintering is terminated after keeping warm for 5 minutes, and the sample is cooled with the furnace, thereby obtaining a high-performance WC-FeNiCo-CeO2 cemented carbide composite material.

2. A method for preparing a synergistically hardened and toughened WC-FeNiCo-CeO2 cemented carbide material as claimed in claim 1, characterized in that: The masses of ammonium metatungstate ((NH4)2WO4) and cerium nitrate (Ce(NO3)3) in the step (1) are calculated based on the contents of WC and CeO2 in the WC-FeNiCo-CeO2 cemented carbide, and the amount of oxalic acid added is 39.0% of the sum of the masses of ammonium metatungstate ((NH4)2WO4) and cerium nitrate (Ce(NO3)3). The heating is performed by oil bath heating at a temperature of 120-150°C.

3. A method for preparing a synergistically hardened and toughened WC-FeNiCo-CeO2 cemented carbide material as claimed in claim 1, characterized in that: The drying oven in step (1) is an electric constant temperature blast drying oven, model DHG-9070, with a temperature set at 80-100°C and a drying time of 8-12 hours. The temperature of the muffle furnace in step (1) is set at 500-600°C and the drying time is set at 4-5 hours.

4. A method for preparing a synergistically hardened and toughened WC-FeNiCo-CeO2 cemented carbide material as claimed in claim 1, characterized in that: In the step (1), the composite precursor powder is reduced in a high-temperature tubular atmosphere furnace to generate W-CeO2 composite powder at a reduction temperature of 800-900°C, a reduction time of 2-3 hours, and a hydrogen flow rate of 4m 3 / h.

5. A method for preparing a synergistically hardened and toughened WC-FeNiCo-CeO2 cemented carbide material as claimed in claim 1, characterized in that: In the step (2), the mass ratio of Fe powder, Ni powder and Co powder is 1:2:

2.

6. A method for preparing a synergistically hardened and toughened WC-FeNiCo-CeO2 cemented carbide material as claimed in claim 1, characterized in that: The ball mill in step (2) is a QM-QX4 omnidirectional planetary ball mill produced by Nanjing University of Science and Technology. The ball mill speed (rotation speed) is 350 rpm, the ball-to-material ratio is set to 10:1, the ball milling time is set to 30 h, the ball tank and the ball milling medium are both made of cemented carbide, and the drying oven in step (2) is an electric constant temperature blast drying oven, model DHG-9070, the temperature is set to 80-100 ° C, and the drying time is 8-12 h.

7. A method for preparing a synergistically hardened and toughened WC-FeNiCo-CeO2 cemented carbide material as claimed in claim 1, characterized in that: The amount of carbon black added in step (3) is configured according to 6.14% of the total mass of the W-CeO2 composite powder, the dry mixing time in the planetary ball mill is 4-8 hours, the rotation speed is set to 300-400 r / min, and the ball-to-material ratio is set to 10:

1. The tungsten-carbon composite powder in step (3) is loaded into an alumina crucible and placed in a high-temperature tubular atmosphere furnace. The high-temperature carbonization temperature is 1400-1550°C, the reaction time is 2-3 hours, and the hydrogen flow rate is 4m 3 / h, and after cooling in the furnace, the composite powder is ground and sieved through 80 mesh to obtain WC-CeO2 composite powder. The amount of FeNiCo powder added in step (3) is configured according to 10% of the total mass of the WC-FeNiCo-CeO2 composite powder. The powder is wet-milled in a planetary ball mill for 30-40h, with the rotation speed set at 350 r / min and the ball-to-material ratio set at 10:

1.

8. A method for preparing a synergistically hardened and toughened WC-FeNiCo-CeO2 cemented carbide material as claimed in claim 1, characterized in that: The drying oven in step (3) is an electric constant temperature blast drying oven, model DHG-9070, with a temperature setting of 80-100°C and a drying time of 8-12 hours.

9. A method for preparing a synergistically hardened and toughened WC-FeNiCo-CeO2 cemented carbide material as claimed in claim 1, characterized in that: In the step (4), the diameter of the graphite mold is 25 mm, and carbon paper is used to isolate the WC-FeNiCo-CeO2 final-treated composite powder from the graphite mold to facilitate sampling and demoulding after sintering. The pre-compacting pressure in step (4) is 20 MPa, and infrared temperature measurement is used during sintering, with the infrared detector aligned with the temperature measuring hole of the graphite mold.

10. A method for preparing a synergistically hardened and toughened WC-FeNiCo-CeO2 cemented carbide material as claimed in claim 1, characterized in that: The spark plasma sintering furnace model in step (4) is LaboxTM-300, and the setting program is as follows: increase the temperature to 600°C at a rate of 100°C / min, the sintering pressure is 20MPa, and keep warm for 5 minutes; then increase the temperature to 1230°C at a rate of 100°C / min, during which the pressure is increased from 20MPa to 40MPa, keep warm for 5 minutes, and then cool with the furnace.

Citation Information

Patent Citations

  • Preparation method of FeCoCu medium-entropy alloy binding phase hard alloy

    CN114574726A

  • Preparation method of rare earth WC-CoFeNi hard alloy

    CN116532645A

  • Medium-entropy ferric sodium pyrophosphate composite material and preparation method thereof

    CN118458731A

  • Preparation method of cemented carbide with iron, cobalt and copper medium-entropy alloy as binding phase

    US11718899B1